Pemanfaatan ChatGPT dalam Meningkatkan Keterampilan Menulis/Maharah Kitabah Berbasis 6C (Critical Thinking, Creativity, Collaboration,Communication, Computational and Compassion) - Yasmar, Renti; Suja, Aidillah; Hidayat, Ahmad Fadhel Syakir (Al-Jawhar : Journal of Arabic Language, 2023)
ChatGPT with its ability to produce text with good systematics raises its own debate among education experts. Both in the form of support and concerns that lead to rejection of this AI technology. This study looks at opportunities to use ChatGPT in improving writing / maharah kitabah  skills based on the 6 C's (Critical Thinking, Creativity, Collaboration, Communication, Computational and Compassion). The research method used is a quasi-experimental design with pretest-posttest design and questionnaires to collect student response data. and using quantitative and qualitative data analysis techniques.  The study began by describing experimental steps in using ChatGPT in improving writing / maharah kitabah skills  based on the 6Cs of Critical Thinking, Creativity, Collaboration, Communication, Computational and Compassion. The results of this study were (1) there was a significant difference from the pretest score which was smaller than the posttest value of 50.45 < 81.50, (2) based on the N-gain formula there was an increase of about 62.6% from the pre-test score to the post-test with the category quite increased. Based on the data analysis conducted, it was concluded that the use of ChatGPT is quite effective in improving writing skills / maharah kitabah based on 6 C. In addition, from the results of ChatGPT student responses make it easier to compile and plan writing, ChatGPT helps in improving grammar skills and sentence structure, ChatGPT provides feedback in improving writing, ChatGPT can increase creativity and diversity of writing styles,  and ChatGPT helps speed up the writing process.